1994
DOI: 10.1161/01.atv.14.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ultrasound-measured common carotid artery stiffness with pathological findings.

Abstract: To quantitatively and noninvasively evaluate common carotid atherosclerosis in a series of patients, we measured the stiffness parameter p, which represents the mechanical properties of the vessel. /3 was calculated from the relationship between blood pressure and the diameter of the artery as measured by an ultrasonic, phase-locked, echotracking system. Increases in the severity grade of atherosclerosis as subsequently determined at autopsy were correlated with increased Rvalues in 60 common carotid arteries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(102 citation statements)
references
References 8 publications
3
92
0
7
Order By: Relevance
“…22 Obese humans have increased leptin production per unit of fat mass 13 and consequently disproportionately elevated leptin concentrations. 14 We measured arterial distensibility, which is known to correlate closely with atherosclerotic risk factors 4 -7,10 -12 (even from a young age 7,25 ), extent of disease, 8,9 and cardiovascular risk. 34 The association of arterial distensibility with leptin was independent of fat mass and metabolic and inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Obese humans have increased leptin production per unit of fat mass 13 and consequently disproportionately elevated leptin concentrations. 14 We measured arterial distensibility, which is known to correlate closely with atherosclerotic risk factors 4 -7,10 -12 (even from a young age 7,25 ), extent of disease, 8,9 and cardiovascular risk. 34 The association of arterial distensibility with leptin was independent of fat mass and metabolic and inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, obesity has been associated with lower arterial distensibility, 4 -7 a measure of the elastic properties of the vessel wall, and an index of circulatory function relevant to the atherosclerotic process. 8,9 Furthermore, weight loss has been shown to improve arterial stiffness. 4,10,11 It is not clear, however, whether obesity has a direct influence on arterial distensibility or whether its adverse effects are mediated by risk factors associated with obesity, such as insulin resistance 6,12 or inflammation.…”
mentioning
confidence: 99%
“…Furthermore, a strong correlation between arterial stiffness and the development of atherosclerosis at various sites in the arteries has been noted. 35,36 Therefore, measuring arterial stiffness can be an important clinical tool for the monitoring of disease progression and treatment efficacy, as recommended by the European Network for Non-invasive Investigation of Large Arteries 25 and the 2007 European guidelines for the management of arterial hypertension. 26 The use of arterial stiffness measurements may be particularly useful in assessing the endothelial damage induced by certain cardiovascular risk factors, such as OSA.…”
Section: Therapeutic and Clinical Implicationsmentioning
confidence: 99%
“…33 A strong correlation between arterial stiffness and the development of atherosclerosis at various sites in the arterial tree has been noted. [34][35][36] In fact, a recent study showed that arterial stiffness is an early marker of atherosclerosis, as it is affected to a greater extent when compared with intima-media thickness in patients with vascular disease. 37 This result is in line with another study, which showed that arterial stiffness is an independent predictor of vascular health and coronary artery disease above and beyond intima-media thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Increased arterial stiffness is also associated with hypertension, diabetes mellitus (DM), end-stage renal disease and atherosclerosis. [1][2][3][4][5][6] Recently, it has also been shown to be associated with increased risk of cardiovascular disease. [7][8][9] The extent of the increase in stiffness may depend on various factors; it is likely that genetic variations play a role.…”
Section: Introductionmentioning
confidence: 99%